Legal Antinomy in the Implementation of Government Contract Dispute Resolution with Private Parties - Wening Galih Pitaloka (Proceedings Series on Social Sciences & Humanities, 2023)
The procurement of goods and services for the benefit of the state is one of the means of driving the wheels of the economy to increase the prosperity of the national economy, because the acquisition of goods and services by the government is intended for public services. Public procurement of goods/services carried out through contracts between the government and the private sector, in addition to being subject to civil jurisdiction, is also subject to public sector rules. This research aims to discuss the implementation of dispute resolution of goods and services procurement contracts between the Government and private parties with regard to the application of public law and private law. This research is written using the normative juridical method through a Legislation and case approach using binding primary legal materials and secondary legal materials as references. The result of this research is that legal efforts to resolve disputes between the government and private parties in civil case law, namely by litigation and non-litigation, are generally carried out with public law and civil law because they are carried out for the implementation of government functions. So to overcome the problems that often arise in the field, this is regulated in the Arbitration and Alternative Dispute Resolution Law No. 30 of 1999 which regulates the procedures for resolving disputes between contracting parties. In addition, the provisions for contract termination, especially public goods/services contracts, are also contained in Presidential Regulation No. 16/2018.